2013
DOI: 10.1159/000346383
|View full text |Cite
|
Sign up to set email alerts
|

Volume Expansion Does Not Alter Cerebral Tissue Oxygen Extraction in Preterm Infants with Clinical Signs of Poor Perfusion

Abstract: Background: Preterm infants with signs of poor perfusion are often treated with volume expansion, although evidence regarding its effect on cerebral perfusion is lacking. Moreover, the effect is questionable in preterm infants with an adequate cerebrovascular autoregulation (CAR). A useful measure to assess perfusion is cerebral fractional tissue oxygen extraction (cFTOE). Objectives: To assess the effect of volume expansion on cFTOE in preterm infants with signs of poor perfusion. Methods: In this observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…It is possible that the parameters other than a numerical threshold for low BP may better identify infants at risk for a poor outcome who would benefit from therapy. Incorporation of indirect measures of systemic or cerebral blood flow may also partially explain the observed variability in BP management, including why some infants without low BP received an antihypotensive therapy while other infants with low BP did not 3 14 22 23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the parameters other than a numerical threshold for low BP may better identify infants at risk for a poor outcome who would benefit from therapy. Incorporation of indirect measures of systemic or cerebral blood flow may also partially explain the observed variability in BP management, including why some infants without low BP received an antihypotensive therapy while other infants with low BP did not 3 14 22 23…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, factors beyond the immediate postnatal period may have more influence on toddler age outcomes thus masking the impact of early BP management on neurodevelopment 25. Lastly, given the complexity of the immature cardiovascular system, antihypotensive therapies may inconsistently influence cardiac function such that they do not uniformly alter early postnatal cerebrovascular blood flow or oxygen delivery 18 22 23…”
Section: Discussionmentioning
confidence: 99%
“…Also, the absolute blood pressure values may not correlate with cerebral perfusion [88,89]. Interestingly, cerebral oxygenation has been shown to predict neurodevelopmental outcome better than the presence of hypotension defined by absolute blood pressure values [90].…”
Section: Cerebral Oxygenation To Guide Clinical Managementmentioning
confidence: 99%
“…Near-infrared spectroscopy allows the measurement of cerebral regional oxygen saturation (crSO 2 ) and calculation of cerebral fractional tissue oxygen extraction (cFTOE) [14] by taking SpO 2 into account. Fractional oxygen extraction represents the relation between oxygen delivery and oxygen consumption; cFTOE can be used as a proxy for cerebral fractional oxygen extraction and decreases until minute 5 after birth [12,15,16], and CBF depends on vascular resistance and blood pressure. An observational study in extremely low birth weight infants has demonstrated a pressure dependent cerebral oxygenation, indicating an impaired control of cerebral vascular resistance and dysfunction of cerebral autoregulation during the first week of life [17].…”
Section: Introductionmentioning
confidence: 99%